Association of T715P (RS6136), M62I (RS2228315), S290N (RS6131), V640L (RS6133) polymorphisms in the P-selectin gene and its ligand with acetylsalicylic acid resistance in patients with coronary artery disease after coronary artery bypass grafting - A. A. Kosinova; T. S. Mongush; M. D. Goncharov; T. N. Subbotina; K. S. Semashchenko; G. Yu. Kochmareva; Yu. I. Grinshtein (Российский кардиологический журнал)
Aim. To study the association of T715P (rs6136), M62I (rs2228315), S290N (rs6131), V640L (rs6133) polymorphisms in the P-selectin gene with resistance to acetylsalicylic acid (ASA) in patients with coronary artery disease after coronary artery bypass grafting (CABG).Material and methods. The study included 90 patients aged 61,5±6,9 years (70 men and 20 women) with II-IV functional class (FC) angina pectoris, according to the Canadian Cardiovascular Society grading. The atherosclerotic nature of coronary artery disease is confirmed by coronary angiography. Patients stopped taking antiplatelet agents before CABG for at least 5 days. The aggregation study was carried out with an optical aggregometer using ADP inducers (5 pM) and arachidonic acid (1 µМ) before CABG, on 1-3 and 8-10 days after surgical treatment.DNA samples were examined for the presence of T715P (rs6136), M62I (rs2228315), S290N (rs6131), V640L (rs6133) polymorphisms in the P-selectin gene using realtime PCR with allele-specific primers.Results. When comparing aPTT, fibrinogen level, platelet aggregation activity with ADP inducers (5 µМ) and arachidonic acid (1 µМ), no differences were found among groups of patients with homozygous and heterozygous variants of the studied polymorphisms genotypes, both before and on 1-3, 8 -10 days after CABG. Regarding presence of ASA resistance, patient groups with homozygous variants of genotypes (T715P (rs6136), M62I (rs2228315), S290N (rs6131), V640L (rs6133)) did not statistically differ in prevailing or rare alleles from the corresponding groups with heterozygous genotypes. In the first 10 days of the postoperative period, thrombotic events (4,4%) were observed in 4 patients in the study group: acute myocardial infarction, acute cerebrovascular accident. Regarding frequency of adverse events in the first 10 days after CABG, between groups of patients with homozygous variants of the studied genotypes (T715P (rs6136), M62I (rs2228315), S290N (rs6131), V640L (rs6133) in prevailing allele and groups with heterozygous variants of the corresponding genotypes there were also no statistically significant differences.Conclusion. Rs6133, rs6163, rs2228315, rs6131 polymorphisms in the platelet P-selectin gene are not associated with ASA resistance and are not associated with increased platelet aggregation activity in patients with coronary artery disease. The rare T, C, G, A alleles of the studied polymorphisms do not lead to an increase in the risks of adverse events in the first 10 days after CABG.